Deep-sequencing of Marburg virus genome during sequential mouse passaging and cell-culture adaptation reveals extensive changes over time - Haiyan Wei (Nature Portfolio, 2017)
Abstract Marburg virus (MARV) has caused outbreaks of filoviral hemorrhagic fever since its discovery in 1967. The largest and deadliest outbreak occurred in Angola in 2005, with 252 cases and 227 deaths. In 2014, we developed a mouse-adapted MARV, Angola variant through serial passaging in mice. The mouse-adapted MARV exhibits many of the hallmarks of MARV disease in humans. By applying deep-sequencing to every passage of the virus, we are able to study virus evolution in this host with surprising precision. We show that two regions go through substantial changes: the intergenic region between NP and VP35, as well as the first 100 amino acids of the VP40 protein. Our results also reveal that there were profound changes during the production of the final virus stock in cell culture. Overall, our results show that a handful of regions carry most of the mutations acquired during the adaptation of the virus to a new host and that many mutations become fixed very early during the adaptation process.